The influence of cultivated land transfer and Internet use on crop rotation - Liang, Chang’an; Du, Guoming; Faye, Bonoua (Frontiers in Sustainable Food Systems, 2023)
In the context of China’s digital transformation and agricultural modernization, exploring the impact of cultivated land transfer and Internet use on crop rotation holds significant importance for promoting sustainable use of cultivated land and ensuring the supply of agricultural products. This study utilizes an ordered logistic regression model to investigate this issue, based on a social survey of 489 households in Heilongjiang Province. Our findings reveal that (1) cultivated land transfer and Internet use both promote crop rotation, but cultivated land transfer is more efficient than Internet use. In addition, two-years cultivated land transfer are more effective than one-year, (2) The analysis of the mechanism indicates that both have the most significant promotion effect in the maize-soybean transition zone, and the promotion effect of cultivated land transfer is mainly observed in the older age group, while Internet use is mainly observed in the younger age group. As aging farmers become more critical, the role of cultivated land transfer does not change significantly, while the role of Internet use decreases. Furthermore, the interaction effect of cultivated land transfer and Internet use is not conducive to crop rotation in the maize-soybean transition zone, but it can facilitate crop rotation in older age groups.